Establishment of a New Political Party in the Center of Hegemony National Political Parties (Challenges and Opportunities) Casuistics of the People's Wave Party in Asahan District - Bayu Raditya; Farhan Indra (Journal of Law, Politic and Humanities, 2024)
In a democratic system, political parties play an important role in decision-making and government administration. However, in Indonesia, national political parties have consolidated hegemony, so local and regional parties focus on increasing their influence. This makes new political parties in the national political system significant, especially for parties that come from weak and under-resourced regions.The method that researchers use in this research is qualitative research which aims to gain an in-depth understanding of the phenomenon being studied. By choosing this research method, it aims to dig deeper into establishing a new political party in the midst of the hegemony of national political parties (challenges and opportunities) of the People's Wave Party case in Asahan Regency.The results of research that have been carried out using interview techniques with the chairman of the DPD People's Wave Party of Asahan Regency are expected to get in-depth answers as well. After carrying out the interview. From the results of the interview, information was obtained about establishing a new political party in the midst of the hegemony of national political parties (challenges and opportunities) of the People's Wave Party case in Asahan Regency.The conclusion of the results of this study shows that the Gelora Party is faced with special and complex challenges in establishing itself in the midst of the hegemony of national political parties. Intense competition with established national political parties is the main obstacle for the Gelora Party.